Comparative study of ultimate saturation velocity in zigzag and chiral carbon nanotubes - Chek, D. C. Y. (American Institute of Physics, 2011)
Charge transfer mechanism in carbon nanotubes (CNTs) from the scattering-limited Ohmic transport to high-field-initiated ballistic transport is studied. It is shown that the electrons changes their motion from randomness (in equilibrium) to streamlined one (in non-equilibrium) when high electric field is applied. The intrinsic velocity is discussed in non-parabolic semiconducting limits considering the nondegenerate and degenerate situations. The results obtained are significant in extracting carrier transport properties from experimental data on CNTs and in understanding the fundamental processes controlling the charge transport in nanoscale devices.